Early Life Nutrition as a Determinant of Long-Term Vaccine Immunogenicity in Livestock: Mechanisms, Practical Strategies, and Species-Specific Considerations - Md. Emran Hossain (International Journal of Vaccines, 2026)
Early life represents a critical period for immune system development in livestock, during which nutritional exposures can exert long lasting effects on vaccine immunogenicity. Although vaccination is a cornerstone of infectious disease control in food producing animals, marked variability in vaccine induced immune responses is frequently observed under commercial conditions. Growing evidence suggests that this variability is partly driven by differences in early nutritional status, which can influence immune maturation, antigen processing, and the establishment of immunological memory. This review examines the role of early life nutrition as a determinant of long-term vaccine immunogenicity in livestock. Emphasis is placed on the impact of colostrum intake, milk and milk replacer composition, early solid feed introduction, and key micronutrients on primary and secondary vaccine responses. Mechanistic pathways through which early nutrition modulates vaccine outcomes are discussed, including effects on lymphoid organ development, cytokine signalling, gut associated lymphoid tissue maturation, and microbiota driven immune regulation. Evidence from poultry, swine, cattle, and small ruminants is synthesized to highlight species specific patterns as well as common nutritional principles influencing vaccine performance. The review also addresses the consequences of early nutritional deficiencies and metabolic stress on vaccine hypo responsiveness, antibody persistence, and booster efficacy. Attention is given to the interaction between maternal immunity, early feeding practices, and vaccine timing. Finally, current knowledge gaps and methodological limitations are identified, and future research directions are proposed to support precision nutritional strategies aimed at improving vaccination outcomes. By integrating nutritional and immunological perspectives, this review underscores the importance of early life feeding management as a modifiable factor for enhancing long term vaccine immunogenicity and improving the sustainability of livestock health programs.
Keywords: Antibody response; Livestock; early life nutrition; immune programming; vaccine immunogenicity